Ethnomedicinal, Pharmacological, and Phytochemical Overview of Diplazium esculentum - Abhishek Singh (RGUHS Journal of Medical Sciences)
Diplazium esculentum commonly known as lsquoVegetable fernrsquo or lsquoPakorsquo holds significant traditional medicinal value across tropical and subtropical regions. This comprehensive review synthesizes existing literature to provide an in-depth exploration of its ethnomedicinal pharmacological and phytochemical properties. The ethnomedicinal section elucidates its traditional uses in treating ailments like fever inflammation gastrointestinal disorders and wound healing drawing upon centuries-old indigenous knowledge from diverse cultures. Pharmacologically D. esculentum exhibits multifaceted activities including antioxidant properties antimicrobial effects against a spectrum of pathogens hepatoprotective potential and emerging evidence suggesting antidiabetic activity. Phytochemical analysis reveals the presence of various bioactive compounds notably polyphenols such as flavonoids and phenolic acids triterpenoids alkaloids and saponins which contribute to its therapeutic potential and biological activities. Mechanistic insights delve into molecular pathways elucidating the interactions of D. esculentum bioactives with cellular targets and signalling cascades. Furthermore pharmacokinetic considerations shed light on the absorption distribution metabolism and excretion ADME profiles of its constituents providing critical insights into their bioavailability and pharmacological efficacy. Evaluation of the safety profile through animal studies and clinical trials underscores its potential as a safe therapeutic agent albeit with considerations for dosage and administration. Clinical applications encompass a wide range of conditions including gastrointestinal disorders infectious diseases liver ailments and metabolic disorders suggesting promising avenues for integrative medicine approaches. Formulation strategies and standardization methods are discussed to ensure product quality and consistency while future research directions emphasize the need for mechanistic elucidation clinical validation and sustainable utilization of D. esculentum in both traditional healing practices and modern pharmacotherapy. This review consolidates existing knowledge facilitating a deeper understanding of D. esculentums therapeutic potential and fostering interdisciplinary collaboration for its continued exploration and utilization in global health contexts.